Shock Index Values and Trends in Pediatric Sepsis: Predictors or Therapeutic Targets? A Retrospective Observational Study. Issue 3 (September 2016) - Ray, Samiran; Cvetkovic, Mirjana; Brierley, Joe; Lutman, Daniel H.; Pathan, Nazima; Ramnarayan, Padmanabhan; Inwald, David P.; Peters, Mark J.
Abstract : Supplemental Digital Content is available in the text ABSTRACT: Background: Shock index (SI) (heart rate [HR]/systolic blood pressure [SBP]) has been used to predict outcome in both adult and pediatric sepsis within the intensive care unit (ICU). We aimed to evaluate the utility of SI before pediatric ICU (PICU) admission. Patients and Methods: We conducted a retrospective observational study of children referred to a pediatric intensive care transport service (PICTS) between 2005 and 2011. The predictive value of SI, HR, and blood pressure at three prespecified time points (at referral to PICTS, at PICTS arrival at the referring hospital, and at PICU admission) and changes in SI between the time points were evaluated. Death within the first 48 h of ICU admission (early death) was the primary outcome variable. Results: Over the 7-year period, 633 children with sepsis were referred to the PICTS. Thirty-nine children died before transport to a PICU, whereas 474 were transported alive. Adjusting for age, time points, and time duration in a multilevel regression analysis, SI was significantly higher in those who died early. There was a significant improvement in SI with the transport team in survivors but not in nonsurvivors. However, the predictive value of a change in SI for mortality was no better than either a change in HR or blood pressure. Conclusions: The absolute or change in SI does not predict early death any more than HR and SBP individually in children with sepsis.